2013
DOI: 10.1248/yakushi.13-00173
|View full text |Cite
|
Sign up to set email alerts
|

The Elucidation of the Function and the Expression Control Mechanism of Aquaporin-3 in the Colon

Abstract: Aquaporins (AQPs) are membrane channels that transport water within the human body and are therefore important for the regulation of water homeostasis. However, little is known regarding the details of the physiological role of AQP3, which is predominantly expressed in the colon. Thus, we investigated the role of AQP3 in the colon using laxative agents (magnesium sulfate and bisacodyl). The results suggest that the laxative eŠect produced by magnesium sulfate, which is classiˆed as an osmotic laxative, is not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…In addition, suppression of AQP-3 function may lead to diarrhea by increasing the fecal water content. Furthermore, the purgative action of magnesium sulfate changes the osmotic pressure and downregulates AQP-3 expression in mucosal epithelial cells of the colon, resulting from activation of adenylate cyclase by increasing the intracellular magnesium ion concentration (20,26). In the present study, normal rat colon tissues expressed low levels of AQP-3.…”
Section: Discussionsupporting
confidence: 44%
See 1 more Smart Citation
“…In addition, suppression of AQP-3 function may lead to diarrhea by increasing the fecal water content. Furthermore, the purgative action of magnesium sulfate changes the osmotic pressure and downregulates AQP-3 expression in mucosal epithelial cells of the colon, resulting from activation of adenylate cyclase by increasing the intracellular magnesium ion concentration (20,26). In the present study, normal rat colon tissues expressed low levels of AQP-3.…”
Section: Discussionsupporting
confidence: 44%
“…AQPs may participate in the adjustment of intestinal mucosal permeability and the rate of water absorption. Abnormalities of AQPs are known to be associated with Crohn's disease, ulcerative colitis, slow transit constipation and cholera (18)(19)(20)(21)(22)(23)(24). A previous study (12) and the results of the present study demonstrated that the expression of AQPs in colon tissues during SAP increased significantly, but in a diverse manner, and a negative correlation between AQP expression and the MAP was determined.…”
Section: Discussionmentioning
confidence: 99%
“…The inhibition of AQP1, AQP3, AQP8, and AQP10 in the ileum has shown the imbalance of water absorption and secretion. With a high casein diet, the expression of some aquaporins becomes inhibited, thereby increasing the fecal water content, and ultimately inducing diarrhea [46,47]. AQPs played an important role in the transition during diarrhea in many tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, AQP3 localization has been observed in the large intestine at the level of the stratified and basolateral epithelia in the distal colon [26,28,29,51] and in the rectum, whereas no signal detection was found in the caecum [52]. AQP4 has also been found in humans, albeit with a very low immunoreactive signal [21].…”
Section: Aqp Structure and Distribution In Gutmentioning
confidence: 99%